Preparation and characterization of hydroxyapatite (HA) from cow bone and its composite with poly (lactic acid) for bone replacement - Akindoyo, John Olabode (2018)
The wide application of hydroxyapatite (HA) for medical applications such as bone tissue replacement sometimes constitutes environmental challenges as the conventional HA synthesis routes require the use of organic solvents. On the other hand, the current trend of research is to incorporate biomaterials such as HA into polymer matrices for some medical applications such as bone replacements. However, this often produces composites with inferior properties. This is due to poor HA dispersion within the composites as well as compatibility issues. In this study, natural HA was produced from cow bone through ultrasound and calcination processes at various temperatures. Composites then were produced from poly (lactic acid) (PLA) and hydroxyapatite (HA) through extrusion and injection molding. In order to foster good interaction between PLA and HA, and to impart antimicrobial properties onto the HA, surface of the HA was modified. On the other hand, impact properties of the PLA-HA composite was improved through the incorporation of impact modifier. Characterization of the produced HA was carried out through thermogravimetric (TGA) and field emission scanning electron microscope (FESEM) analysis. Spectrum obtained for the HA through Fourier Transform Infrared Spectroscopy was also compared with standard HA. Likewise, X-ray diffraction analysis of the HA in comparison with International Centre for Diffraction Data (ICDD) index for standard HA was conducted. On the other hand, Ca/P ratio of the produced HA was verified through Energy Dispersive X-ray analysis for elemental analysis. Likewise, different characterization techniques were used to characterize the composite produced. These include Fourier transforms infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC), Dynamic Mechanical Analysis (DMA), tensile, flexural and impact analysis. Also microbial properties of the produced HA and its composite with PLA were assessed. In addition, in vitro biocompatibility study was used to assess the cell attachment and cell proliferation properties of the composites. Results showed that modification of HA led to increased HA dispersion within the PLA matrix, which resulted into significantly higher mechanical, thermal and dynamic mechanical properties of the resulting composite. Similarly, impact properties of the PLA-HA composite was remarkably improved after incorporation of biostrong impact modifier. In addition, in vitro study revealed that the PLA-HA composite exhibits good biocompatibility properties. In general, the results from this study shows that combination of the salient properties of HA with the good mechanical properties of PLA holds great potential for production of bone replacement composite materials with good load bearing ability. The composite produced herein can help to overcome the secondary operation procedures often associated with the conventional bone replacement procedures.